Reversing the rural race to the bottom: an evolutionary model of neo-endogenous rural development - Martin Petrick (European Review of Agricultural Economics, 2013)
The article contributes to the understanding of neo-endogenous rural development from the perspective of evolutionary game theory. Rural development is modelled as the increasing realisation over time of gains from interaction by rural stakeholders. The model exhibits two dynamically stable equilibria, which depict declining and prospering regions. An external government authority stimulates neo-endogenous rural development by helping decentralised actors to coordinate on the superior of the two equilibria. This intervention may be possible and desirable without giving up the autonomy of local decision makers. Because initial conditions matter, outcomes cannot be planned or engineered from the outside.
Keywords: C73; R23; R58; 330; rural governance; neo-endogenous rural development; evolutionary game theory; collective action